Respuesta :
Step 1: Remove ()
-6x+18x-9=-69
Step 2: Put like terms on each side (variable x on left, # on right)
-6x+18x=-69+9
Step 3: Add/Subtract like terms
12x=-60
Step 4: Divide each side by 12
x=-5
^Answer
x=-5.
First you expand the form, and it gave us, [tex]3(6x-3)=18x-9[/tex], and [tex]-6x+18x-9=-69[/tex]. Then you add by the similar elements, and it gave us, [tex]-6x+18x=12x[/tex], and [tex]12x-9=-69[/tex]. Next, you add by nine from both sides of equation form. And it gave us, [tex]12x-9+9=-69+9[/tex]. And then you simplify. And it gave us, [tex]12x=-60[/tex]. You can also divide by twelve from both sides of equation form. And it gave us, [tex]\frac{12x}{12}=\frac{-60}{12}[/tex]. And finally, you simplify and it gave us the final answer. And it gave us, [tex]\frac{12x}{12}=x[/tex], [tex]\frac{-60}{12}=-5[/tex], and [tex]x=-5[/tex]. x=-5 is the final answer. Hope this helps! And thank you for posting your question at here on brainly, and have a great day. -Charlie